2020
DOI: 10.21203/rs.3.rs-45314/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cutaneous manifestations associated with COVID-19 in children: A Systematic Review

Abstract: Background: Cutaneous manifestation of COVID 19 in children has not yet been reviewed systematically and hence this review gives a future direction to the clinicians to be vigilant for skin presentations during such pandemic.Methodology: The review was done as per the guidelines of PRISMA and literature search was done on PubMed database using keywords as COVID-19, children and skin in different combinations. Articles published in English with cases of age 1 month to 18 years were eligible. The outcome include… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…Therefore, in addition to respiratory and GI manifestations, dermatological manifestations, cutaneous vessel vasculitis, and conjunctivitis can be expected with this infection. Infected children are usually asymptomatic or have a few general symptoms that can be due to innate immune system with higher number of T, B and NK cells; lower number of ACE‐2 receptor with less affinity to SARS‐CoV‐2; less pro‐inflammatory cytokine response; and possible role of Bacillus Calmette–Guérin vaccination in protection against virus 4‐6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to respiratory and GI manifestations, dermatological manifestations, cutaneous vessel vasculitis, and conjunctivitis can be expected with this infection. Infected children are usually asymptomatic or have a few general symptoms that can be due to innate immune system with higher number of T, B and NK cells; lower number of ACE‐2 receptor with less affinity to SARS‐CoV‐2; less pro‐inflammatory cytokine response; and possible role of Bacillus Calmette–Guérin vaccination in protection against virus 4‐6 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, many of the infected children are overlooked that leads to more spreading of the disease. Since the COVID‐19 pandemic, there are several case reports and case series characterizing skin manifestations in children with mild respiratory and gastrointestinal (GI) symptoms or in asymptomatic ones who had household contact with COVID‐19 5 . In one systematic review by Hoang et al, the prevalence of dermatological manifestations of COVID‐19 was estimated as 0.25% in 2445 children with confirmed COVID‐19 and the prevalence of skin manifestations was reported as 3% in 100 children in another study by Parri et al in Italy 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Rates of positive COVID testing were low across all reviews with 92% negative in Shah et al 6 and negative in almost all cases in Andina et al and Molaee et al 2,3 Andina et al reported that most cases were not associated with extracutaneous manifestations (ECM) of COVID-19 infection, 2 whereas other reviews reported respiratory or gastrointestinal symptoms and fever. 6,7 All cases in Andina et al had spontaneous regression of CLL without complications, with resolution times ranging from 12 days to over 8 weeks 2 ; similarly Khalili et al reported that CLL usually resolved without treatment after 7 to 10 days. 7 Despite available data on CLL in pediatric patients, a comprehensive summary of CLL during the early COVID-19 pandemic is lacking.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, Andina et al (2021) 2 reported that CLL usually occurred in children over ten years of age, with an approximately equal male-female ratio. 2 CLL predominantly affected the feet and occasionally the hands, 2,3,6,7 and sometimes were associated with symptoms of pruritus, tenderness, pain, a burning sensation, tingling, or coldness. 7 Rates of positive COVID testing were low across all reviews with 92% negative in Shah et al 6 and negative in almost all cases in Andina et al and Molaee et al 2,3 Andina et al reported that most cases were not associated with extracutaneous manifestations (ECM) of COVID-19 infection, 2 whereas other reviews reported respiratory or gastrointestinal symptoms and fever.…”
Section: Introductionmentioning
confidence: 99%
“…Las lesiones cutáneas por SARS-CoV-2 suelen presentarse en niños y adolescentes saludables, rara vez en niños menores de 10 años y aparecen en los pies en 74 a 100 % de los casos, si bien también han sido descritas en manos y dedos. 1,2,3,4,5,6,7 Suelen ser múltiples, redondas y varían de tamaño, de pocos milímetros a centímetros, afectando a todo el dedo del pie, con una clara demarcación a nivel del metatarso-falange. Se han observado manchas, edema y lesiones eritematosas, violáceas o purpúricas, que pueden parecer infiltrantes.…”
Section: Introductionunclassified